REVIEW: INTERACTION OF GLIMEPIRIDE WITH HERBAL PLANTS - Nurjaman, Jajang; Sulaeman, Agus (Universitas Muhammadiyah Ahmad Dahlan Cirebon, 2025)
Glimepiride is a commonly prescribed oral antidiabetic drug for the management of type 2 diabetes mellitus (T2DM). However, extensive simultaneous use of herbal plants increases the risk of notable interactions between herbs and drugs. This systematic review analyzed the pharmacokinetic and pharmacodynamic interactions between glimepiride and various medicinal plants, based on 20 selected studies published between 2014 and 2024. The results show that several herbs including Berberine hydrochloride, Licorice, Quercetin, Aloe vera, Ocimum sanctum, and Fenugreek can alter glimepiride’s metabolism, enhance its bioavailability, and increase insulin secretion, potentially amplifying its hypoglycemic effect. Although these interactions may improve therapeutic outcomes, they also increase the risk of hypoglycemia, indicating that careful monitoring and professional supervision are essential when using herbal supplements alongside glimepiride. Keywords: Pharmacokinetic pharmacodynamics, glimepiride interaction, herbal plants.